POLA PIKIR GURU DALAM MENYAMPAIKAN PEMAHAMAN KONSEP PEMBELAJARANMATEMATIKA - Mutazam Mutazam; Sri Asih Agustin, Poniam (Adiba Aisha Amira, 2022)
Not understanding the concepts that students receive is one of the things that makes mistakes in learning mathematics. Apart from that, it can be said that the teacher failed in carrying out learning. Therefore, on this occasion we will discuss the Teacher's Mindset in Conveying Mathematics Learning Concepts. Objective: Teacher's Mindset in Conveying Understanding of Mathematics Learning Concepts. Method: problem solving using a qualitative descriptive approach by conducting community service research. Results: In overcoming misconceptions in mathematics learning, it is necessary to analyze the obstacles that influence misconceptions so that quick solutions can be provided to overcome the problems found.